1974
DOI: 10.1016/0022-2836(74)90378-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the viral proteins on the fluidity of the membrane lipids in Sindbis virus

Abstract: The fluidity of the lipids in the membrane of Sindbis virus was studied by electron paramagnetic resonance spectroscopy. The lipids in the viral membrane are noticeably less fluid than the lipids in the membrane of the cells in which the virus was grown. This difference in fluidity is not due simply to differences in lipid composition but instead appears to be the result of the interaction of the viral proteins with the membrane lipids. This conclusion seems clear because (i) the viral lipids are more fluid af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0

Year Published

1975
1975
2008
2008

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(33 citation statements)
references
References 34 publications
3
30
0
Order By: Relevance
“…PE is known to have a higher gel-fluid phase transition temperature than phosphatidylcholines (PCs) and is likely to convert to s o . For example, the typical monounsaturated PE species, POPE (5) and SOPE (6) Lipid membranes of influenza viruses were previously studied using fluorescent 13,14 and spin labels 10,11 . The early spin label study of influenza virus 12 aimed only at determination of whether the influenza envelope contains a lipid bilayer, but the study detected less 'fluidity' in the influenza membrane than in the erythrocyte membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PE is known to have a higher gel-fluid phase transition temperature than phosphatidylcholines (PCs) and is likely to convert to s o . For example, the typical monounsaturated PE species, POPE (5) and SOPE (6) Lipid membranes of influenza viruses were previously studied using fluorescent 13,14 and spin labels 10,11 . The early spin label study of influenza virus 12 aimed only at determination of whether the influenza envelope contains a lipid bilayer, but the study detected less 'fluidity' in the influenza membrane than in the erythrocyte membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The influenza virus has played a pivotal role in the development of the raft hypothesis, starting with early studies that inferred ordered domains using spin probes [10][11][12] and fluorescence 13,14 and that suggested that an ordered lipid domain is selected in toto as the envelope during budding from the plasma membrane 15 . These lipids are either selected at the time of budding or pre-selected as the 'pre-envelope' suggested by clusters of the viral envelope protein hemagglutinin seen in immunoelectron microscopy 16 .…”
mentioning
confidence: 99%
“…The factors that have been demonstrated to affect the order parameter of the fatty acid spin labels in membranes include lipid composition (4,5), the presence of some membrane proteins (6)(7)(8), anesthetics (26,27), and interaction of membranes and membrane receptors with certain drugs and small molecules (10,11 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, the flexibility of lipid chains is not always determined by chemical composition alone, but may also be affected by the presence of proteins in the intact membrane. As an example, the motions of the lipids in Sindbis virus are dominated by the presence of the viral proteins (8). Thus, the question of whether differences in glycoprotein mobility may be correlated with measurable differences in lipid motion can best be answered by measurements of lipid motion in the intact cell membranes.…”
mentioning
confidence: 99%
See 1 more Smart Citation